Pemanfaatan Arus Air untuk Pembangkit Listrik Tenaga Micro Hidro - Jandri Fan HT Saragi; Jhon Sufriadi Purba (CERED Indonesia Publishing, 2021)
One of the problems being faced in several regions in Indonesia is the source of electrical energy. The demand for electricity from year to year has increased. The development of free energy technology needs to be developed to cover the rapidly increasing demand for electricity. One that can be developed is micro-hydro power plant technology that utilizes water flow as a source of electricity. To make a micro hydro power plant, it is necessary to do research on the available discharge and how much energy and power is generated at that location. The purpose of this community service activity is to help the community find out the potential of river flows in Toba Village, South Siantar District, Pematangsiantar City in its utilization for micro hydro power plants. The method of implementing the activity is Head observation (falling height), river flow velocity, river width, and river flow depth. From the results of observations and measurements of discharge at the service location, it is known that the head (fall height) is 0.5 meters, the river flow speed is 0.74 m/s, the river width is 6.5 meters and the river flow depth is 0.3 meters so that an empirical calculation of the generator discharge is obtained at 1.433 m3/sec., and the power that can be generated is 7.08 kW.